1992
DOI: 10.1161/01.str.23.10.1420
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythmicity of stroke onset. Intracerebral and subarachnoid hemorrhage.

Abstract: Our purpose was to describe and further understand the determinants of the time of onset of parenchymatous intracerebral hemorrhage and subarachnoid hemorrhage in patients enrolled in the Stroke Data Bank. We analyzed the observed times of onset of intracerebral hemorrhage (n = 237 patients) and subarachnoid hemorrhage (n = 243 patients) compared with expected times of onset if the probability of onset was constant across all time intervals. We also analyzed the role of clinical features (if any) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
65
2
6

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 35 publications
9
65
2
6
Order By: Relevance
“…2,4,6,11,12,14,15,17,18,20,22,24,26,27,[29][30][31][32][33] Hospital-based and populationbased studies that demonstrated significant seasonal variation found that the peak period for SAH differed widely. [4][5][6]15,20,24,26,32,33) No statistically significant seasonal variations were also observed in some studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,4,6,11,12,14,15,17,18,20,22,24,26,27,[29][30][31][32][33] Hospital-based and populationbased studies that demonstrated significant seasonal variation found that the peak period for SAH differed widely. [4][5][6]15,20,24,26,32,33) No statistically significant seasonal variations were also observed in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6]15,20,24,26,32,33) No statistically significant seasonal variations were also observed in some studies. 2,12,14,17,22,27,[29][30][31] The highest occurrences of SAH were found in spring in women and in late fall in men, 4) in spring and fall in men, and in winter in women, 24) and in winter in women and no peak in men. 32) Our data resembled the results of 10 years of the Canadian Collaborative Study Group although the lowest occurrence in their male group was in summer whereas that of in the present study was in winter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maintenance of blood pressure reduction during the first hours of the morning, after the patient wakes up, is another major point to be considered, because the most likely peak time for cardiovascular events occurs between 06:00-11:00 [2][3][4][5] . The goals for blood pressure levels have become increasingly rigorous.…”
Section: A Multicenter Open-label Study Of the Efficacy And Safety Omentioning
confidence: 99%
“…2,4,7,13,15) However, other studies have not found significant seasonal variation or meteorological association. 1,10,14,[22][23][24] Interpretation of such results is complicated by the multiple factors associated with the design of each study, including the number of patients studied, criteria for patient selection (based on onset, admission, surgical treatment, or death), method of sampling (community-based or hospital-based), and the statistical method used for the analysis. In addition, the complexity of the physical factors which may influence the process of aneurysmal rupture could also cause the conflicting results.…”
Section: Introductionmentioning
confidence: 99%